Preterm birth prevention-Time to PROGRESS beyond progesterone. - Jane E Norman; Phillip Bennett (PLoS Medicine)
In a Perspective, Jane Norman and Phillip Bennett argue that it is time to explore alternatives to progesterone for preventing preterm birth.